Influencia del carburo de calcio y el tiempo de aireación en la recuperación de oro por cianuración en agitación de un mineral aurífero-arsenical - Arana Chávez, Robert Amilcar (2019)
In the following research work the influence of the calcium carbide dosage and the aeration time on the percentage of gold recovery of an arsenical flotation gold tailings was studied. The independent variables are: dosage of calcium carbide with levels 0, 3 and 6 Kg / TM and the aeration time at 0, 30 and 60 minutes. The flotation tailings made the granulometric analysis with # 200 mesh, then the grinding curve was made to obtain 80% through # 400 mesh, then the pulp milling was done by adding 0.5 Kg of tailings to 67% solids and adding calcium carbide as per test; the pulp was discharged into a vessel to stir and insufflate air according to the established levels, then the cyanidation was done in the bottle for 24 hours at 5000 ppm of NaCN; At the end, the solids were washed, dried and analyzed by means of Fire Assay and a mixed method for calculating gold recovery. From the result of the tests, it can be concluded that for the recovery of gold, the highest value is obtained at a dose of 3 Kg / MT of calcium carbide and 60 minutes of aeration with 26.36% recovery of gold and being the highest under 5.26% without dosing calcium carbide or aeration. With the analysis of variance at a 95% confidence level, it is shown that the variables studied significantly influence the recovery of gold from an arsenical gold tailings from flotation